Analisis Pengaruh Perilaku Kebersihan terhadap Risiko Dermatitis pada Kaki Petani Jeruk di Berastagi - Suryani Situmeang; Digna Renny Panduwati; Karolina br Surbakti (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: Dermatitis is a common skin health problem among farmers and is associated with personal hygiene practices in humid working conditions and exposure to agricultural chemicals. Objective: This study aims to analyze the relationship between hygiene practices and the risk of dermatitis in the feet of orange farmers in Berastag. Methods: The study design employed a descriptive-analytical approach using a cross-sectional method. The study sample consisted of 30 orange farmers selected via purposive sampling. Data were collected through interviews, observation of hygiene behaviors (foot washing, use of personal protective equipment/PPE, and workplace cleanliness), as well as clinical and mycological laboratory examinations. Results: The study found that 13 respondents (43.3%) had dermatitis, while 17 respondents (56.7%) did not. A total of 19 farmers (63.7%) were in the habit of washing their feet after work, 9 people (30%) used PPE, and 12 people (73.4%) maintained workplace hygiene. Analysis indicated a trend that farmers who did not wash their feet were more likely to experience dermatitis (72.7%) compared to those who did (26.3%). The use of PPE and workplace hygiene were also associated with the occurrence of dermatitis. Laboratory identification revealed pathogenic fungi such as Trichophyton rubrum and Candida albicans, which were implicated in the cases of dermatitis. Conclusion: Hygiene practices are associated with the risk of dermatitis among citrus farmers.